2018
DOI: 10.1002/ptr.6077
|View full text |Cite
|
Sign up to set email alerts
|

Combination of artemisinin‐based natural compounds from Artemisia annua L. for the treatment of malaria: Pharmacodynamic and pharmacokinetic studies

Abstract: Currently, the most effective antimalarial is artemisinin, which is extracted from the leaves of medicinal herb Artemisia annua L. (A. annua). Previous studies showed that the complex chemical matrix of A. annua could enhance both the bioavailability and efficacy of artemisinin. The present study aims to evaluate the efficacy and pharmacokinetic properties of a combination therapy based on artemisinin and 3 components from A. annua with high content (arteannuin B, arteannuic acid, and scopoletin). In vivo anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…artesunate, A. annua (DLA) eliminated parasites within a few days even in comatose pediatrics (Daddy et al, 2017). Studies showed that the numerous phytochemicals in A. annua and A. afra provide synergies and multiple interactions, likely constituting a polytherapy against malaria (Elford et al, 1987;Li et al, 2018;Liu et al, 1992;Suberu et al, 2013). Together, those data and this study indicate that artemisinin is not the sole phytochemical demonstrating antimalarial efficacy by Artemisia sp.…”
Section: Artemisinin Drug Resistancementioning
confidence: 60%
“…artesunate, A. annua (DLA) eliminated parasites within a few days even in comatose pediatrics (Daddy et al, 2017). Studies showed that the numerous phytochemicals in A. annua and A. afra provide synergies and multiple interactions, likely constituting a polytherapy against malaria (Elford et al, 1987;Li et al, 2018;Liu et al, 1992;Suberu et al, 2013). Together, those data and this study indicate that artemisinin is not the sole phytochemical demonstrating antimalarial efficacy by Artemisia sp.…”
Section: Artemisinin Drug Resistancementioning
confidence: 60%
“…The transfer of knowledge from academic research to clinical use can take many years. Given the urgency of the current pandemic, the existence of previous pharmacokinetic, pharmacodynamic, and cytotoxicity studies of A. annua and its compounds are additional factors that make them interesting candidates for drug repurposing [23] , [24] , [25] . Thus, due to the multifunctional properties of A. annua and artemisinins against different viruses and their strong safety profiles, their applicability as an anti-SARS-CoV-2 seems promising and should be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more researchers—including our team—have paid attention to the therapeutic activities of A. annua multi-components in the treatment of malaria [22]. A recent study found that the combination of Art B, AA, scopoletin and Art could improve the efficacy of Art [23,24,25]. Therefore, sesquiterpenoids are the most specific compounds for the treatment of malaria.…”
Section: Discussionmentioning
confidence: 99%